2004
DOI: 10.1158/1055-9965.epi-03-0273
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR Polymorphisms, Dietary Folate Intake, and Breast Cancer Risk

Abstract: Folate plays an important role in DNA methylation, synthesis, and repair; intake has been associated with breast cancer. The folate-metabolizing enzyme, methylenetetrahydrofolate reductase (MTHFR) is polymorphic at nucleotides 677 (C3 T) and 1298 (A3 C), resulting in allozymes with decreased activity. We evaluated these two common polymorphisms and their effects on the folate intake and breast cancer risk association in a population-based case-control study of 1144 breast cancer cases and 1236 controls using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
210
6
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(243 citation statements)
references
References 28 publications
22
210
6
5
Order By: Relevance
“…Similarly, a meta-analysis including data from our study and 12 previously published studies 5,6,8,9,13,14,27,28 showed no evidence for an overall association for MTHFR E429A (summary OR 5 1.00; 95% CI 0.85-1.17 based on 6,521 cases and 8,515 controls; Table III). Results were similar across racial groups and geographical regions.…”
Section: Meta-analysessupporting
confidence: 64%
See 3 more Smart Citations
“…Similarly, a meta-analysis including data from our study and 12 previously published studies 5,6,8,9,13,14,27,28 showed no evidence for an overall association for MTHFR E429A (summary OR 5 1.00; 95% CI 0.85-1.17 based on 6,521 cases and 8,515 controls; Table III). Results were similar across racial groups and geographical regions.…”
Section: Meta-analysessupporting
confidence: 64%
“…A meta-analysis including data from this study and 21 previously published studies [5][6][7][8][9][10][11][12][13][14][27][28][29][30][31][32][33] showed no association between variant vs. common homozygote genotypes for MTHFR A222V and breast cancer risk [summary OR (95% CI) 5 0.99 (0.86-1.15), based on 8,330 cases and 10,825 controls]. Similarly, a meta-analysis including data from our study and 12 previously published studies 5,6,8,9,13,14,27,28 showed no evidence for an overall association for MTHFR E429A (summary OR 5 1.00; 95% CI 0.85-1.17 based on 6,521 cases and 8,515 controls; Table III).…”
Section: Meta-analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, there is substantial error in the measurement of folate, and intake at a particular time point may not be a good indicator of average lifetime exposure to folate. In two studies of breast cancer and folate intake, the intraclass correlation coefficient for folate intake measured on two occasions was 0.36, 28 and for folate measured by food frequency questionnaire compared with 24 h recall was 0.26. 29 There are promising results from small preliminary randomized controlled trials of folate supplementation and depression.…”
Section: Study Limitationsmentioning
confidence: 99%